Early modernization theory?: the Eisenhower administration and the foreign policy of development in Brazil - Sewell, Bevan (Oxford University Press, 2010)
Existing views of the Dwight D. Eisenhower administration’s policies in Latin America have tended to portray its approach as being either fixated upon waging the Cold War, or overly concerned with quelling outbreaks of Latin American economic nationalism. Eisenhower’s approach has been viewed as regressive and reactionary; more concerned with political stability than economic and social progress. This view, moreover, has been strengthened by the actions of Eisenhower’s successor – John F. Kennedy’s announcement of the Alliance for Progress, and the prominent role played by Modernization Theory in his administration’s approach toward the developing world, have been viewed as a stark contrast to what had come before. This article challenges that prevailing view, however, by examining the Eisenhower administration’s economic policy towards Brazil. In developmental terms, it will be argued, Eisenhower’s approach was not so very different from Kennedy’s: the methods and theoretical underpinnings between the two administrations may have differed, but what they ultimately wanted to achieve – flourishing nation states that were prosperous, pro-American, and ultimately democratic – remained a constant goal. Like Kennedy, Eisenhower’s approach was constructed on a singular belief in the best way for a nation to develop; it was a standpoint that, due to the country’s economic potential, could be most clearly identified in Brazil. In examining Eisenhower’s economic approach toward Brazil, therefore, this article suggests that there is a compelling need for us to reperiodize the era of Modernization with regard to US developmental policy in Latin America.